2017
DOI: 10.1002/ejhf.822
|View full text |Cite
|
Sign up to set email alerts
|

Do patients have worse outcomes in heart failure than in cancer? A primary care‐based cohort study with 10‐year follow‐up in Scotland

Abstract: Aims: To evaluate whether the survival rates of patients with heart failure (HF) in the community are better than those with a diagnosis of the 4 most common cancers in men and women in a contemporary primary care cohort in Scotland. Methods and Results:The data were obtained from the Primary Care Clinical Informatics Unit from a database of 1.75 million people registered with 393 general practices in Scotland. Sex-specific survival modeling was undertaken using Cox proportional hazards models, adjusted for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
165
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(177 citation statements)
references
References 34 publications
2
165
1
9
Order By: Relevance
“…Frequent problems include, but are not limited to, chronic kidney disease, 3,4 liver dysfunction, 5,6 gastrointestinal disease, 7,8 anaemia, 9,10 fatigue, 11,12 infections, 13,14 anorexia 15,16 , muscle wasting, 17,18 pain, 19,20 and heart failure (HF). 23 HF is associated with a 5-year survival rate of nearly 50% [24][25][26] and is frequently accompanied by reduced quality of life. 23 HF is associated with a 5-year survival rate of nearly 50% [24][25][26] and is frequently accompanied by reduced quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent problems include, but are not limited to, chronic kidney disease, 3,4 liver dysfunction, 5,6 gastrointestinal disease, 7,8 anaemia, 9,10 fatigue, 11,12 infections, 13,14 anorexia 15,16 , muscle wasting, 17,18 pain, 19,20 and heart failure (HF). 23 HF is associated with a 5-year survival rate of nearly 50% [24][25][26] and is frequently accompanied by reduced quality of life. 23 HF is associated with a 5-year survival rate of nearly 50% [24][25][26] and is frequently accompanied by reduced quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Although survival rates have improved, the absolute mortality rates for CHF remain approximately 50% within five years of diagnosis (Levy et al, 2002), and this patient group continues to have lower survival rates than patients with common cancers such as breast and prostate cancers (Mamas et al, 2017). Recent…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…Previous like‐for‐like comparisons of heart failure vs. cancer‐related survival have suggested that the former is indeed as ‘malignant’ as the most common forms of cancer with the notable exception of lung cancer, a condition that, like heart failure, has not attracted the attention it most probably deserves. Whether it is still legitimate to label heart failure as malignant as cancer (particularly when considering that previous studies have focused on hospitalized cohorts) is the focus of a study undertaken by Mamas and colleagues . Using population‐based primary care data from Scotland, the authors examined the survival profiles of 56 658 patients newly diagnosed with heart failure or the most common forms of cancer.…”
mentioning
confidence: 99%
“…In women (1‐ and 5‐year mortality of 15% and 40%), heart failure was more ‘malignant’ than breast cancer but not lung, ovarian, and colorectal cancer. As appropriately described in the report, therefore, it is probably legitimate to label heart failure as malignant as many forms of cancer . However, as highlighted by a recent late‐breaking report on 1‐year survival rates within the INTERnational Congestive Heart Failure (INTER‐CHF) Study cohort derived from a range of low‐ and middle‐income countries there is considerable heterogeneity in the profiles and outcomes associated with heart failure across the globe.…”
mentioning
confidence: 99%